Designing Colloidal Molecules with Microfluidics. Issue 6 (25th April 2016) - Shen, Bingqing; Ricouvier, Joshua; Malloggi, Florent; Tabeling, Patrick
Abstract : The creation of new colloidal materials involves the design of functional building blocks. Here, a microfluidic method for designing building blocks one by one, at high throughput, with a broad range of shapes is introduced. The method exploits a coupling between hydrodynamic interactions and depletion forces that controls the configurational dynamics of droplet clusters traveling in microfluidic channels. Droplet clusters can be solidified in situ with UV. By varying the flow parameters, clusters are prescribed a given size, geometry, chemical and/or magnetic heterogeneities enabling local bonding. Compact structures (chains, triangles, diamonds, tetrahedrons, ...) and noncompact structures, such as crosses and T, difficult to obtain with current techniques are produced. Size dispersions are small (2%) and throughputs are high (30 000 h −1 ). The work opens a new pathway, based on microfluidics, for designing colloidal building blocks with a potential to enable the creation of new materials. Abstract : A method of design of colloidal molecules, based on microfluidics, and exploiting a novel hydrodynamical mechanism of self‐assembly, is described. A rich variety of elementary assemblies, enabling the creation of functional colloidal materials, is obtained under excellent control, at high throughput, with a broad range of shapes (diamonds, chains, tetrahedrons).